How to Improve Blue–Green–Gray Infrastructure to Optimize River Cooling Island Effect on Riparian Zone for Outdoor Activities in Summer - Min Wang; Yuqing Su; Jieqiong Wang (Land, 2025)
As important urban green spaces, rivers enhance cooling island effects significantly by leveraging environmental factors. This study selected Suzhou River in Shanghai as the subject to explore how to improve blue–green–gray infrastructure to optimize the river cooling island effect on the riparian zone for outdoor activities in summer. A total of 77 samples, including 36 control groups and 41 experimental groups, were categorized into 12 types of blue–green–gray infrastructure composite features. ENVI-met was used to simulate summer thermal comfort, while redundancy analysis and boosted regression trees were used to identify significant factors and thresholds influencing the river’s cooling island effect. The results showed that for Suzhou River, the green–blue–green–gray–green composition most effectively optimizes the river cooling island effect. It is recommended to select construction sites where the river width is 55 m and the percentage of green infrastructure exceeds 40% and keep the distance between green infrastructure and the water body to within 3 m. Additionally, limiting gray infrastructure to less than 10%, with an average building height of 37 m and a building undulation of 25 m, is recommended to achieve the optimal cooling effect. This study finally proposes optimization strategies to maximize the cooling island effect of urban rivers, offering insights for the development of climate-adaptive urban riparian zones.